PELAKSANAAN PENERTIBAN OPERASIONAL WARUNG INTERNET DI TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Ferdy Martha; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Implementation of Operational Control Internet Cafes In TembilahanIndragiri Hilir. Internet cafes are businesses engaged in services that provide services to thepublic internet fasilitass. Rapidly growing internet cafes in the city Tembilahan. This is in linewith the growing need for access to technology and information and the current era ofglobalization. Of services offered by the internet cafes are popular , social networking sites andonline gaming. This study aims to determine how the factors inhibiting the implementation andoperational control of internet cafes in the city Tembilahan Indragiri Hilir, to conform to theapplicable regulations Indragiri districts downstream regulation number 21 of 2008 concerningpublic order .This study used qualitative methods of data collection techniques by means ofinterviews, observation and study of literature. Interviews were conducted by researchinformants defined by snowball sampling technique. The results found that the implementationof the operational control of internet cafes in Tembilahan kabapaten downstream Indragiri notrun optimally in accordance with the regulations set by the government. It can be seen from thenumber of internet cafes business owners who commit violations such as violations of theoperating hours of internet cafes, many coming pengunjug school attributes, and there are manyvisitors who come under 17 years of age. It all can not be separated from the presence ofobstacles in the implementation of the curb that is, less their cooperation cyber cafe owner ,limited human and financial resources the municipal police, and lack of coordination of theparties concerned .Keywords : Execution , Control , Public Interne